HYDROSTATIC GENERATOR OF NON-PERIODIC PRESSURE IMPULSES FOR TESTING TECHNICAL PRODUCTS - Nizhegorodov, A.I.; Gavrilin, A.N.; Moyzes, B.B.; Ismailov, G.M. (KU Publ., 2021)
The article reviews the possibility of using the hydrostatic generators of oscillators with nonlinear power elements (elastic shells) as part of the structures of various test benches in the field of mechanical tests for vibration strength and vibration resistance, as well as when testing with external and internal pressure. The hydrostatic generator of non-periodic pressure impulses for engineering products testing is a new patented technical solution in the field of testing machines. The ratios of the angular velocities of the shafts, which provides the movement of the operating fluid into the actuator of the test bench in the form of a non-periodic function and with impulses varying in amplitude in a random manner were obtained. It makes a continuous and non-repetitive sequence of pressure impulses and corresponds to the operation of the tested objects in real conditions. The random nature of the amplitudes settings is provided by signals controlled from electric generators through controlled hydraulic valves. The development of a hydrostatic generator with a power element in the form of an elastic shell is represented by a hydromechanical diagram of a generator of non-periodic pressure impulses with corresponding kinematic and dynamic dependencies. In addition, there were developed three hydro-mechanical systems with the use of a new hydrostatic generator for engineering products testing both for mechanical random vibration and for testing the external and internal pressure of engineering objects that operate in such conditions. The result of the research is the expansion of the range of systems and methods for the test processes implementation under random non-periodic force effects on various engineering objects.
Keywords: hydrostatic generator; non-periodic pressure impulses; technical products; testing